Iron carbide / charcoal composite electro-Fenton cathode material and preparation method and application thereof
By using Fe3C/BC electrofenton cathode material and using biochar as a carrier to improve conductivity and molecular oxygen activation ability, the shortcomings of traditional electrofenton technology in removing neonicotinoid pesticide pollutants are solved, and efficient, stable and repeatable degradation effects are achieved.
Patent Information
- Application Number
- CN202510076372.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-01-10
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-17
AI Technical Summary
Traditional homogeneous electrofenton technology has shortcomings such as narrow pH range, easy generation of iron sludge, and unrecyclable catalysts, making it difficult to efficiently remove neonicotinoid pesticide pollutants.
Fe3C/BC electrofenton cathode material is used, which is formed by mixed calcining of iron-based metal organic frame material and straw. It is produced by one-step hydrothermal and simple mixed grinding calcining. Biochar as a support improves the conductivity and molecular oxygen activation ability.
It significantly improves the degradation effect of neonicotinic pesticides, improves the dispersion and stability of electrofenton active sites, reduces metal leakage, improves the stability and reusability of cathode materials, and is applicable to the treatment of water bodies of pollutants of different concentrations.
Smart Images

Figure CN119873967A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to an electric-Fenton cathode material, and specifically relates to an iron carbide / biochar composite electric-Fenton cathode material and a preparation method and application thereof. Background Art
[0002] Neonicotinoid pesticides have become the most widely used class of insecticides in the world. They can be applied to agriculture through spraying and soil irrigation, seeping into soil and groundwater through wind, rain and surface runoff, and eventually entering water bodies, seriously threatening human health and environmental safety. It is worth noting that neonicotinoid pesticides are highly stable in water environments and are difficult to remove through natural photolysis and hydrolysis.
[0003] A large number of studies have shown that advanced oxidation technology has significant advantages in treating organic pollutants in water bodies, among which electro-Fenton technology has attracted much attention due to its green and efficient characteristics. However, the traditional homogeneous electro-Fenton technology mainly has shortcomings such as narrow pH range, easy generation of iron sludge and non-recyclable catalyst. In order to overcome the shortcomings of heterogeneous electro-Fenton technology, heterogeneous electro-Fenton technology has gradually become a research hotspot. Cathode materials are the core of heterogeneous electro-Fenton technology and determine the treatment effect of target pollutants. Metal-organic framework materials have great development potential due to their advantages such as high porosity, low density and large specific surface area. It is worth noting that the skeleton part of metal-organic framework materials contains inorganic metal components, which can serve as the active center of heterogeneous electro-Fenton reaction, and thus have important application value in the degradation of organic pollutants. In addition, metal-organic framework materials can be converted into magnetic derivatives as electro-Fenton cathode materials by high-temperature calcination under inert atmosphere, which is conducive to their recovery and subsequent reuse. However, the shortcomings of metal-organic framework materials such as easy structural collapse, easy destruction of catalytic active sites and easy agglomeration under high temperature conditions limit the performance of metal-organic framework material derivatives. Chinese invention patent CN113620390B discloses a method for catalytic treatment of heavy metal-EDTA complex wastewater using an electrically assisted metal organic framework material, but due to its single magnetic component causing partial agglomeration, it exhibits limited pollutant removal efficiency. Summary of the invention
[0004] Purpose of the invention: In view of the problems existing in the prior art, the present invention provides a Fe3C / BC electro-Fenton cathode material. The Fe3C / BC cathode material prepared by the present invention can not only improve the dispersion and stability of electro-Fenton active sites, but also the good conductivity and molecular oxygen activation ability of BC can accelerate the electron transfer in the system and promote the generation of active substances in the system, thereby significantly improving the degradation effect of neonicotinoid pesticides.
[0005] The present invention also provides a method for preparing a Fe3C / BC electro-Fenton cathode material and application thereof in electro-Fenton degradation of neonicotinoid pesticide pollutants.
[0006] Technical solution: In order to achieve the above purpose, the Fe3C / BC electro-Fenton cathode material of the present invention is formed by mixing and calcining an iron-based metal organic framework material and straw, and the iron-based metal organic framework material accounts for 5%-20% of the mass of the straw.
[0007] Preferably, the iron-based metal organic framework material accounts for 10% of the mass of the straw.
[0008] Wherein, the metallic iron in the Fe3C / BC electro-Fenton cathode material mainly exists in the form of Fe3C.
[0009] The method for preparing the Fe3C / BC electro-Fenton cathode material of the present invention comprises the following steps:
[0010] (1) adding iron salt and diaminoterephthalic acid to an organic solvent, performing a hydrothermal reaction, cooling, washing, and drying to obtain an iron-based metal organic framework material;
[0011] (2) The iron-based metal organic framework material obtained in step (1) and the straw powder are mixed and ground, and calcined in an inert gas to obtain a Fe3C / BC electro-Fenton cathode material.
[0012] Wherein, the iron source in step (1) is selected from any one or more of ferric chloride, ferric nitrate and ferric acetate.
[0013] Wherein, the dosage of the iron salt in step (1) is 8-12% g / mL of the organic solvent N,N-dimethylformamide solvent; the dosage of diaminoterephthalic acid is 2-5% g / mL of the organic solvent N,N-dimethylformamide solvent.
[0014] Wherein, the hydrothermal reaction in step (1) is carried out at 100-180° C. for 12-24 hours.
[0015] Wherein, in step (2), the mass ratio of the iron-based metal organic framework material to the straw is 0.05-0.2:1.
[0016] Preferably, the straw is any one of corn, rice, wheat or sugarcane straw.
[0017] Wherein, the inert gas in step (2) is nitrogen or argon; the heating rate of calcination is 5 to 10° C., the temperature is 500 to 900° C., and the calcination time is 1 to 5 hours.
[0018] The application of the Fe3C / BC electro-Fenton cathode material in electro-Fenton degradation of pollutants.
[0019] The pollutant is nitenpyram, imidacloprid or thiamethoxam, and the electro-Fenton degradation process is carried out in a three-electrode system, wherein the three electrodes are Fe3C / BC-loaded carbon cloth as cathode, Pt sheet as anode, saturated calomel electrode as reference electrode, and nitenpyram aqueous solution containing Na2SO4 as reaction liquid for electro-Fenton degradation experiment, the pH value of the system is 3-9, and the reaction time is 40-60min.
[0020] Preferably, the process of electro-Fenton degradation of acetamiprid by the Fe3C / BC electro-Fenton cathode material is as follows: a three-electrode system is adopted, wherein the three electrodes are respectively carbon cloth loaded with Fe3C / BC as cathode, Pt sheet as anode, saturated calomel electrode as reference electrode, the initial voltage is set to -0.5V, Na2SO4 is used as electrolyte, and electro-Fenton degradation experiment is carried out with acetamiprid as pollutant under oxygen condition, the pH value of the system is adjusted to 3, and the reaction is carried out for 60 minutes.
[0021] The present invention adopts a specific preparation method to prepare Fe3C / BC electro-Fenton cathode material, and is applied to the efficient and rapid degradation of neonicotinoid pesticides. The present invention directly mixes, grinds and calcines the iron-based metal organic framework material with straw, and the iron-based metal organic framework material accounts for 5%-20% of the mass of the straw. The preparation of the Fe3C / BC electro-Fenton cathode material only requires one step of hydrothermal and simple mixed grinding and calcination, and does not require secondary hydrothermal treatment. The steps are simple and the cost is low. In addition, the metallic iron in the Fe3C / BC electro-Fenton cathode material mainly exists in the form of Fe3C rather than metal oxides. In addition, biomass-based carbon is selected as a carrier in the iron-based metal organic framework material of the present invention, so that Fe3C / BC can significantly improve the performance of degrading neonicotinoid pesticides compared to BC obtained by calcining straw alone, and compared with Fe3C obtained by calcining the iron-based metal organic framework material alone, the metal leakage is greatly reduced, and the stability of the cathode material is improved. The Fe3C / BC electro-Fenton cathode material prepared by the present invention has good stability and reusability, strong resistance to water matrix interference, and a wide applicable pH range, and can be applied to the treatment of water bodies with different concentrations of pollutants, and has a fast pollutant degradation rate and a good degradation effect.
[0022] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0023] (1) The Fe3C / BC electro-Fenton cathode material of the present invention can be prepared by only one step of hydrothermal treatment and simple mixing, grinding and calcination, with a simple process and low cost.
[0024] (2) In the Fe3C / BC electro-Fenton cathode material prepared by the present invention, the biomass-based carbon component has strong conductivity, large specific surface area, and excellent reduction ability for molecular oxygen. Using it as a carrier can effectively reduce the agglomeration of electro-Fenton active sites, enhance the current density in the electro-Fenton system, and promote the generation of active substances, thereby significantly improving the degradation effect of neonicotinoid pesticides.
[0025] (3) The Fe3C / BC electro-Fenton cathode material prepared in the present invention has excellent resistance to water matrix interference, is applicable to a wide pH range, and can treat water bodies with different initial concentrations of pollutants, so it has great application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a scanning electron microscope image of the Fe3C / BC electro-Fenton cathode material in Example 1 of the present invention.
[0027] Figure 2 1 and 2 are X-ray diffraction patterns of the electro-Fenton cathode materials in Example 1 and Comparative Example 1 of the present invention.
[0028] Figure 3 This is a diagram showing the degradation effect of the electro-Fenton cathode material on nitenpyram in Examples 1 to 3 of the present invention and Comparative Example 1.
[0029] Figure 4 This is a graph showing the effect of the Fe3C / BC electro-Fenton cathode material loading on the degradation effect of nitenpyram in Example 1 of the present invention.
[0030] Figure 5 This is a diagram showing the degradation effect of nitenpyram by the Fe3C / BC electro-Fenton cathode material at different pH values in Example 1 of the present invention.
[0031] Figure 6 This is a diagram showing the degradation effect of the Fe3C / BC electro-Fenton cathode material on different initial concentrations of acetamiprid in Example 1 of the present invention.
[0032] Figure 7 This is a diagram showing the degradation effect of nitenpyram on the Fe3C / BC electro-Fenton cathode material at different applied potentials in Example 1 of the present invention.
[0033] Figure 8 This is a diagram showing the degradation effect of acetamiprid on the Fe3C / BC electro-Fenton cathode material in Example 1 of the present invention in different water matrices.
[0034] Fig. 9 The cyclic stability of the Fe3C / BC electro-Fenton cathode material in Example 1 of the present invention in degrading acetamiprid.
[0035] Fig.10 This is a performance diagram of the Fe3C / BC electro-Fenton cathode material in Example 1 of the present invention for degrading other neonicotinoid pesticide pollutants.
[0036] Fig.11 This is a diagram showing the degradation effect of nitenpyram by the electro-Fenton cathode material in Example 1 of the present invention and Comparative Examples 1-2.
[0037] Fig.12 The degradation effect of nitenpyram pollutant in different reaction systems.
[0038] Fig.13 The linear sweep voltammetry curves and electrochemical impedance spectra of Fe3C / BC in Example 1 of the present invention and BC in Comparative Example 1 are shown. DETAILED DESCRIPTION
[0039] The experimental methods described in the examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0040] Example 1
[0041] A method for preparing a Fe3C / BC electro-Fenton cathode material comprises the following steps:
[0042] (1) Preparation of metal organic framework materials: 2.7 g FeCl3·6H2O was weighed and added to 30 mL N,N-dimethylformamide (DMF), and 0.9 g diaminoterephthalic acid was weighed and added to 30 mL DMF. After both solutions were dissolved, they were mixed and stirred for 1 h. After that, they were transferred into a reaction vessel with a brown polytetrafluoroethylene liner and subjected to hydrothermal reaction at 110°C for 24 h. After that, they were taken out. After the hydrothermal reaction, the material was washed three times by centrifugation with ethanol, dried overnight in a vacuum drying oven at 60°C, taken out, ground and stored for later use.
[0043] (2) The obtained metal organic framework material and corn straw powder were mixed and ground, put into a crucible and transferred to a tube furnace, the mass ratio of metal organic framework material to corn straw was 0.1:1. High-purity argon gas was introduced and the temperature was raised to 800°C at a rate of 5°C / min and kept for 2h. After the tube furnace was naturally cooled, the sample was taken out to obtain Fe3C / BC electro-Fenton cathode material. In this embodiment, the metal organic framework material accounted for 10% of the mass of the corn straw.
[0044] The microstructure of the Fe3C / BC electro-Fenton cathode material prepared in Example 1 is as follows: Figure 1 As shown in the figure, Fe3C particles are loaded on the biochar surface more evenly.
[0045] Comparative Example 1
[0046] This comparative example is the same as Example 1, except that no iron-based metal organic framework material is added, and corn stalk powder is directly calcined, and the product is recorded as BC.
[0047] Comparative Example 2
[0048] This comparative example is the same as Example 1, except that no corn stalk powder is added, and the iron-based metal organic framework material is directly calcined, and the product is recorded as Fe3C.
[0049] The crystal structure composition of Fe3C / BC prepared in Example 1 and BC prepared in Comparative Example 1 is as follows: Figure 2 As shown, the metallic iron in the Fe3C / BC electro-Fenton cathode material prepared in Example 1 mainly exists in the form of Fe3C.
[0050] Example 2
[0051] This embodiment is the same as embodiment 1, except that the mass ratio of the iron-based metal organic framework material to the corn straw is 0.05: 1. The product is recorded as Fe3C / BC (0.05), and the iron-based metal organic framework material accounts for 5% of the mass of the corn straw in this embodiment.
[0052] Example 3
[0053] This embodiment is the same as embodiment 1, except that the mass ratio of the iron-based metal organic framework material to the corn straw is 0.2:1. The product is recorded as Fe3C / BC (0.2), and the iron-based metal organic framework material accounts for 20% of the mass of the corn straw in this embodiment.
[0054] Example 4
[0055] This embodiment is the same as embodiment 1, except that the hydrothermal time is 12 h and the calcination temperature is 900° C.
[0056] Example 5
[0057] This embodiment is the same as embodiment 1, except that the dosage of the iron salt is 12% g / mL of the N,N-dimethylformamide solvent; and the dosage of the diaminoterephthalic acid is 5% g / mL of the N,N-dimethylformamide solvent.
[0058] Test Example 1
[0059] The degradation effect of the electro-Fenton cathode materials prepared in Examples 1 to 3 of the present invention and Comparative Example 1 on nitenpyram in water was investigated, and the specific method was as follows:
[0060] (1) 6 mg of the electro-Fenton cathode material prepared in Examples 1 to 3 and Comparative Example 1, 300 μL of anhydrous ethanol, 100 μL of water, and 6 μL of Nafion were added to a 1.5 mL centrifuge tube, and after ultrasonication for 40 min, the mixture was evenly coated on a circular hydrophobic and breathable carbon cloth with a diameter of 2.9 cm, and air-dried for later use.
[0061] (2) The electro-Fenton degradation experiment was carried out using a three-electrode system in a gas diffusion electrode under oxygen flow conditions at an oxygen flow rate of 10 mL / min. The three electrodes were Fe3C / BC-loaded carbon cloth as the cathode, Pt sheet electrode as the anode, and saturated calomel electrode as the reference electrode. The initial voltage was set to -0.5 V and the reaction was carried out for 60 min.
[0062] (3) Using Na2SO4 solution as the electrolyte, a 5 mg / L nitenpyram aqueous solution containing 0.05 M Na2SO4 was used for electro-Fenton degradation experiment. The concentration change of nitenpyram during electro-Fenton degradation was measured by liquid chromatography. The results are as follows: Figure 3 As shown, the Fe3C / BC prepared by the present invention can significantly improve the ability to degrade nitenpyram compared with BC alone. At the same time, the mass ratio of the metal organic framework material to the straw in the cathode material prepared by the present invention is very important. Too much or too little metal organic framework material will significantly affect the material's ability to degrade nitenpyram. Among them, the metal organic framework material accounts for 10% of the straw mass and has the best effect. Not only is the degradation effect significantly better than the metal organic framework material accounting for 5% or 20% of the straw mass, but the degradation rate is also significantly improved.
[0063] Test Example 2
[0064] The effect of the loading of the Fe3C / BC electro-Fenton cathode material prepared in Example 1 of the present invention on the degradation performance of nitenpyram pollutants was investigated. The steps for implementing the electro-Fenton degradation process were the same as those in Experimental Example 1, except that the amounts of Fe3C / BC electro-Fenton cathode material were weighed to be 2 mg, 4 mg, 6 mg, and 8 mg, respectively. The results are shown in FIG. Figure 4 As shown in the figure, when the cathode material loading was 6 mg, the degradation rate of acetamiprid pollutant was the highest.
[0065] Test Example 3
[0066] The degradation performance of the Fe3C / BC electro-Fenton cathode material prepared in Example 1 of the present invention on different initial concentrations of nitenpyram pollutants was investigated. The electro-Fenton degradation process was implemented in the same steps as in Example 1, except that the initial concentrations of nitenpyram pollutants were 5 mg / L, 10 mg / L, 20 mg / L, and 40 mg / L, respectively. The results are shown in FIG. Figure 5 As shown, when the initial concentration of acetamiprid pollutant is in the range of 5-40 mg / L, its efficient degradation can be achieved, which indicates that the Fe3C / BC electro-Fenton cathode material has a wide range of initial concentration applicability in removing acetamiprid pollutants from water bodies.
[0067] Test Example 4
[0068] The performance of the Fe3C / BC electro-Fenton cathode material prepared in Example 1 of the present invention in degrading nitenpyram pollutants at different pH values was investigated. The electro-Fenton degradation steps were the same as those in Example 1, except that the initial pH values were adjusted to 3, 5, 7, and 9, respectively, when preparing the solution. The results are shown in FIG. Figure 6 As shown, the nitenpyram pollutant can be effectively degraded in the pH range of 3 to 9, which indicates that the Fe3C / BC cathode material prepared by the present invention has a wide pH applicability. Furthermore, the Fe3C / BC electro-Fenton cathode material prepared by the present invention can quickly degrade nitenpyram in a system with a pH of 3, achieving a degradation effect of more than 90% in 25 minutes, and can be completely degraded after 40 minutes, proving that the present invention can quickly degrade nitenpyram under acidic conditions.
[0069] Test Example 5
[0070] The ability of the Fe3C / BC electro-Fenton cathode material prepared in Example 1 of the present invention to degrade pollutants at different applied potentials was investigated. The electro-Fenton degradation steps were the same as those in Example 1, except that the applied potentials were -0.2V, -0.5V, -0.8V, and -1.1V, respectively. The results are shown in FIG. Figure 7 As shown in the figure, with the increase of applied potential, the degradation efficiency of acetamiprid pollutant gradually increased and the trend was stable.
[0071] Test Example 6
[0072] The ability of the Fe3C / BC electro-Fenton cathode material prepared in Example 1 of the present invention to degrade pollutants in different water matrices was investigated. The electro-Fenton degradation steps were the same as those in Example 1, except that the ultrapure water was replaced with tap water and lake water when preparing the pollutant solution. Figure 8 As shown, the Fe3C / BC electro-Fenton cathode material prepared in the present invention has excellent resistance to water matrix interference and can be used to remove acetamiprid pollutants in various water bodies.
[0073] Test Example 7
[0074] The cyclic stability of the Fe3C / BC electro-Fenton cathode material prepared in Example 1 of the present invention for degradation of nitenpyram was investigated. The specific method was as in Experimental Example 1. After each cycle, the electrode surface was rinsed with water and the degradation experiment was repeated. The results were as follows: Fig. 9 After 4 cycles, the degradation rate of nitenpyram by the catalyst was still maintained at nearly 80%.
[0075] Test Example 8
[0076] The degradation performance of the Fe3C / BC electro-Fenton cathode material prepared in Example 1 of the present invention on other neonicotinoid pesticide pollutants was investigated. The electro-Fenton degradation process was implemented in the same steps as in Example 1, except that the pollutants were replaced by imidacloprid (IMI) and thiamethoxam (TMX) respectively from nitenpyram. The results are shown in Table 1. Fig.10 As shown, the Fe3C / BC electro-Fenton cathode material prepared in Example 1 of the present invention also has an excellent degradation effect on other neonicotinoid pesticides.
[0077] Test Example 9
[0078] The degradation effects of Fe3C / BC in Example 1 of the present invention, BC in Comparative Example 1 and Fe3C in Comparative Example 2 on nitenpyram were investigated. The specific method is the same as that in Experimental Example 1, except that the cathode materials are different. The test results are as follows: Fig.11 As shown in a, compared with single BC, the Fe3C / BC cathode material in Example 1 of the present invention has a significant advantage in degradation efficiency of nitenpyram pollutants. Although the degradation effect of single Fe3C on nitenpyram pollutants is slightly better than that of Fe3C / BC, its metal leakage is nearly 10 times that of Fe3C / BC ( Fig.11 b). Therefore, considering both degradation efficiency and stability, the Fe3C / BC electro-Fenton cathode material prepared by the present invention has more advantages.
[0079] Test Example 10
[0080] The materials prepared in Example 1 were used in this test example. The implementation process of the adsorption system (adsorption) in this test example is the same as that in Test Example 1, with the only difference being that no voltage is applied. The implementation process of the anodic oxidation system (anode oxidation) in this test example is the same as that in Test Example 1, with the only difference being that the gas introduced into the reaction solution is nitrogen. The implementation process of the heterogeneous electro-Fenton system (hetero-EF) in this test example is the same as that in Test Example 1. The implementation process of the homogeneous electro-Fenton system (homo-EF) in this test example is the same as that in Test Example 1, with the only difference being that the cathode in the system is pure carbon cloth, no material is coated on its surface, and homogeneous iron ions (0.2 mg / L) are added to the reaction solution. The degradation performance of the acetamiprid pollutant in the above system is shown in the following figure. Fig.12 As shown in a, after 60 minutes of reaction, the degradation rates of nitenpyram in the heterogeneous electro-Fenton system, adsorption system, anodic oxidation system and homogeneous electro-Fenton system were 75.8%, 2.4%, 38.6% and 27.2%, respectively. In addition, the degradation reaction rate constants of nitenpyram in these systems were 0.02367min -1 、0.0004min -1、 0.0084min -1 and 0.0053min-1 ( Fig.12 b) These results confirm the leading role of the heterogeneous electro-Fenton system, namely the Fe3C / BC cathode material prepared in the present invention, in the degradation of nitenpyram pollutants.
[0081] Test Example 11
[0082] 4 mg of the electro-Fenton cathode material prepared in Example 1 and Comparative Example 1, 600 μL of anhydrous ethanol, 400 μL of water, and 30 μL of Nafion were added to a 1.5 mL centrifuge tube, and evenly coated on the glassy carbon electrode after ultrasonication for 40 minutes, and air-dried for use. The entire characterization process adopts a three-electrode system, in which the three electrodes are glassy carbon electrodes loaded with Fe3C / BC and BC as cathodes, Pt sheet electrodes as anodes, and saturated calomel electrodes as reference electrodes. The linear sweep voltammetric curve was carried out in a 0.05MNa2SO4 aqueous solution with a pH of 3 under the condition of oxygen (10 mL / min). The electrochemical impedance spectroscopy test process is as follows: 4 mg of the electro-Fenton cathode material prepared in Example 1 and Comparative Example 1, 600 μL of anhydrous ethanol, 400 μL of water, and 30 μL of Nafion were added to a 1.5 mL centrifuge tube, and evenly coated on the glassy carbon electrode after ultrasonication for 40 minutes, and air-dried for use. The whole characterization process adopts a three-electrode system, in which the three electrodes are Fe3C / BC and BC loaded glassy carbon electrode as cathode, Pt sheet electrode as anode, and saturated calomel electrode as reference electrode. The whole test is carried out in 0.1M KOH (pH 13) solution under nitrogen (10mL / min) conditions. The test results are shown in Fig.13 As shown in a, compared with single BC, Fe3C / BC cathode material has stronger oxygen reduction activity. In addition, the Fe3C / BC electro-Fenton cathode material prepared by the present invention has smaller electron transfer resistance and mass transfer resistance ( Fig.13 b).
[0083] Test Example 12
[0084] In summary, the present invention adopts the material prepared in Example 1, according to the method of Test Example 1, wherein the amount of Fe3C / BC electro-Fenton cathode material is weighed to be 6 mg, and the electro-Fenton degradation experiment is carried out in a gas diffusion electrode using a three-electrode system, wherein the three electrodes are Fe3C / BC-loaded carbon cloth as cathode, Pt sheet electrode as anode, saturated calomel electrode as reference electrode, and Na2SO4 solution as electrolyte. A 5 mg / L acetamiprid aqueous solution containing 0.05 M Na2SO4 is taken for the electro-Fenton degradation experiment, the pH value of the system is adjusted to 3, the initial voltage is set to -1.1 V, and the degradation rate of acetamiprid can reach 100% within 10 minutes of reaction.
Claims
1. A Fe3C / BC electro-Fenton cathode material, characterized in that: The Fe3C / BC electro-Fenton cathode material is formed by mixing and calcining an iron-based metal organic framework material and straw, wherein the iron-based metal organic framework material accounts for 5% to 20% of the mass of the straw.
2. The Fe3C / BC electric Fenton cathode material according to claim 1, characterized in that: The metallic iron in the Fe3C / BC electro-Fenton cathode material preferably exists mainly in the form of Fe3C.
3. A method for preparing the Fe3C / BC electro-Fenton cathode material according to claim 1, characterized in that: The steps include: (1) adding iron salt and diaminoterephthalic acid to an organic solvent, performing a hydrothermal reaction, cooling, washing, and drying to obtain a metal organic framework material; (2) The metal organic framework material obtained in step (1) and the straw powder are mixed and ground, and calcined in an inert gas to obtain a Fe3C / BC electro-Fenton cathode material.
4. The preparation method according to claim 3, characterized in that: The iron source in step (1) is selected from any one or more of ferric chloride, ferric nitrate and ferric acetate.
5. The preparation method according to claim 3, characterized in that: The amount of the iron salt added in step (1) is 8-12% g / mL of the organic solvent N,N-dimethylformamide solvent; the amount of diaminoterephthalic acid added is 2-5% g / mL of the organic solvent N,N-dimethylformamide solvent.
6. The preparation method according to claim 3, characterized in that: The hydrothermal reaction in step (1) is carried out at 100-180° C. for 12-24 hours.
7. The preparation method according to claim 3, characterized in that: In step (2), the mass ratio of the metal organic framework material to the straw is 0.05-0.2:
1.
8. The preparation method according to claim 3, characterized in that: In step (2), the inert gas is nitrogen or argon; the heating rate of calcination is 5 to 10° C., the temperature is 500 to 900° C., and the calcination time is 1 to 5 hours.
9. Use of the Fe3C / BC electro-Fenton cathode material according to claim 1 in electro-Fenton degradation of neonicotinoid pesticide pollutants.
10. The use according to claim 9, characterized in that: The pollutant is nitenpyram, imidacloprid or thiamethoxam, and the electro-Fenton degradation process is carried out in a three-electrode system under oxygen conditions, wherein the three electrodes are respectively a Fe3C / BC-loaded carbon cloth as a cathode, a Pt sheet as an anode, and a saturated calomel electrode as a reference electrode, and a nitenpyram solution containing sodium sulfate is used as a reaction liquid for the electro-Fenton degradation experiment, the pH value of the system is 3-9, and the reaction time is 40-60 minutes.
Citation Information
Patent Citations
Macro film and fiber consisting of nanocapsules and nanotubes and preparation method thereof
CN103173723A
Preparation method of heterogeneous Fenton catalyst Fe3C / C composite material
CN108404947A
Biomass carbon-based composite catalyst as well as preparation method and application thereof
CN116497396A
Preparation method of charcoal-iron-based metal organic framework composite material for removing perfluorinated pollutants
CN117467151A
Bonding method for part
JP1991221324A
Cited By
LSC-coated Fe3C composite material modified electrode and preparation method and application thereof
CN121476339A